Associations of adherence to Mediterranean-like diet pattern with incident rosacea: A prospective cohort study of government employees in China - Chen, Peng; Yang, Ziye; Fan, Zhihua; Wang, Ben; Tang, Yan; Xiao, Yi; Chen, Xiang; Luo, Dan; Xiao, Shuiyuan; Li, Ji; Xie, Hongfu; Shen, Minxue (Frontiers in Nutrition, 2023)
Background Despite of growing evidence on gastrointestinal comorbidities of rosacea, there was a lack of literatures regarding the role of diet on rosacea. Objectives To investigate the relationship between adherence to a Mediterranean-like diet pattern and the risk of incident rosacea. Methods This was a prospective cohort study of government employees aged >20 years conducted between January 2018 and December 2021 from five cities of Hunan province of China. At baseline, participants completed a food frequency questionnaire and participated in a skin examination. Presence of rosacea was determined by certified dermatologists. Subsequent skin examinations during follow-up were performed every one-year interval since the entry of the study. The Mediterranean diet score (MDS) was generated based on seven food groups (whole grains, red meats, fish, raw vegetables, legumes, fruits and nuts). Binary logistic regression models adjusted for potential confounders were used to estimate risks for incident rosacea. Results Of the 3,773 participants who completed at least two consecutive skin examinations, 3,496 were eligible for primary analyses. With a total follow-up of 8,668 person-years, we identified 83 incident rosacea cases. After full adjustments for covariates, the MDS was associated a decreased risk of incident rosacea (aOR: 0.84, 95% CI: 0.72, 0.99; Ptrend = 0.037 for 1-point increment of MDS). In subgroup analyses by body mass index (BMI), this inverse association was consistently observed in the lowest and medium tertiles of BMI (<24.5 kg/m2), but not in the highest tertile of BMI (≥24.5 kg/m2), with a significant interaction effect (P < 0.001). Conclusions Our results suggested that adherence to a Mediterranean-like diet pattern might reduce the risk of incident rosacea among non-overweight individuals.